2016
DOI: 10.1002/cphc.201501093
|View full text |Cite
|
Sign up to set email alerts
|

High‐Pressure Raman and Calorimetry Studies of Vanadium(III) Alkyl Hydrides for Kubas‐Type Hydrogen Storage

Abstract: Reversible hydrogen storage under ambient conditions has been identified as a major bottleneck in enabling a future hydrogen economy. Herein, we report an amorphous vanadium(III) alkyl hydride gel that binds hydrogen through the Kubas interaction. The material possesses a gravimetric adsorption capacity of 5.42 wt % H2 at 120 bar and 298 K reversibly at saturation with no loss of capacity after ten cycles. This corresponds to a volumetric capacity of 75.4 kgH2  m(-3) . Raman experiments at 100 bar confirm that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 32 publications
5
12
0
Order By: Relevance
“…3D) are endothermic and do not increase or decrease significantly with increased surface coverage. This supports the mechanism discussed at length previously and supported by computations and high-pressure Raman measurements [15][16][17] in which the 20-40 kJ mol À1 H 2 energy expected for Kubas binding of hydrogen 8,9 is offset by twisting of the material as the pressure increases to open up new binding sites. 26 A MOF has been reported that undergoes structural deformation on application of pressure and this deformation influences the adsorption properties.…”
Section: Resultssupporting
confidence: 87%
See 4 more Smart Citations
“…3D) are endothermic and do not increase or decrease significantly with increased surface coverage. This supports the mechanism discussed at length previously and supported by computations and high-pressure Raman measurements [15][16][17] in which the 20-40 kJ mol À1 H 2 energy expected for Kubas binding of hydrogen 8,9 is offset by twisting of the material as the pressure increases to open up new binding sites. 26 A MOF has been reported that undergoes structural deformation on application of pressure and this deformation influences the adsorption properties.…”
Section: Resultssupporting
confidence: 87%
“…This method of synthesizing a solid-state transition metal hydride from a metal alkyl has been reported previously by our group for Ti, Cr, and V systems. [14][15][16][17] The resulting black air sensitive solid (KMH-1 as synthesized) still contained hydrocarbon as evidenced by the infrared (IR) spectrum ( Fig. S1, ESI †) and because of this was hydrogenated in the solid state at 373 K and 85 bar for 4 hours to give KMH-1 after 1st hydrogenation.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations